IMPLEMENTASI MODEL UTAUT UNTUK ANALISIS FAKTOR YANG MEMENGARUHI MINAT PEMANFAATAN DAN PERILAKU PENGGUNAAN SISTEM INFORMASI - Mesra Betty Yel; Sari Agustia Ningtyas (Journal of Information System, Applied, Management, Accounting and Research, 2019)
Based on the results of the discussion of the analysis carried out in this study, it turns out that the UTAUT method is a method that can be used to determine what factors influence the utilization interest and behavior of using the Executive Information System (EIS). In addition, the UTAUT method can also explain how the relationship between the dependent variable and the independent variable. Variables that influence the interest in utilization are Business Expectancy (Effort Expectancy) with a T-statistic value of 3,659 and Social Influence with a T-Statistic value of 3,299. While the variables that influence the Usage Behavior are Facilitating Conditions with the T-Statistic value 2,659 and the Interest in Using (Behavioral Intention) with the T-Statistics value 4,459. The relationship between variables in the UTAUT model is as follows: a. Performance Expectancy (Performance Expectancy) does not affect EIS's Behavioral Intention, b. Business Expectancy (Effort Expectancy) has a significant and positive influence on EIS (Behavioral Intention) interest. c. Social Influence has a significant and positive influence on EIS (Behavioral Intention) interest. d. Facilitating Condition has a significant and positive influence on the behavior of using (Use Behavior) EIS, e. Interest Using (Behavioral Intention) has a significant and positive influence on the behavior of using (Use Behavior) EIS. The percentage level of user acceptance of EIS within the Customs and Excise Head Office is 81.92%.